Geotechnical Risk - World Bank (World Bank, Washington, DC, 2021)
This Technical Note is prepared to provide guidance to the World Bank task teams and clients regarding geological and geotechnical issues and recommended risk mitigation and management measures. The investigation, design, and construction of dams should identify and consider all potential hazards and threats to dam safety while being cognizant of the associated consequences of dam failure.